2009
DOI: 10.1186/1423-0127-16-16
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin (DHA) induces caspase-3-dependent apoptosis in human lung adenocarcinoma ASTC-a-1 cells

Abstract: Background: Dihydroartemisinin (DHA), a semi-synthetic derivative of artemisinin, isolated from the traditional Chinese herb Artemisia annua, is recommended as the first-line anti-malarial drug with low toxicity. DHA has been shown to possess promising anticancer activities and induce cancer cell death through apoptotic pathways, although the molecular mechanisms are not well understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
105
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 36 publications
5
105
0
Order By: Relevance
“…These results were in agreement with previous studies that showed that SLAK exerted an anti-inflammatory effect in J774A.1 macrophages through the inhibition of NO and PGE 2 production as well iNOS and COX-2 expression (Emami et al, 2010). Moreover, the overall impact of these changes also reflect results of previous studies that demonstrated that various individual sesquiterpene compounds from Artemisia exert anti-inflammatory effects that may be effective in treating some types of experimental inflammation/autoimmune conditions (Choi et al, 2011;Ho et al, 2014;Kim et al, 2002;Lu et al, 2009;Omer et al, 2007;Sun et al, 2010;Yang et al, 2012).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results were in agreement with previous studies that showed that SLAK exerted an anti-inflammatory effect in J774A.1 macrophages through the inhibition of NO and PGE 2 production as well iNOS and COX-2 expression (Emami et al, 2010). Moreover, the overall impact of these changes also reflect results of previous studies that demonstrated that various individual sesquiterpene compounds from Artemisia exert anti-inflammatory effects that may be effective in treating some types of experimental inflammation/autoimmune conditions (Choi et al, 2011;Ho et al, 2014;Kim et al, 2002;Lu et al, 2009;Omer et al, 2007;Sun et al, 2010;Yang et al, 2012).…”
Section: Discussionsupporting
confidence: 82%
“…Different classes of chemicals, e.g., coumarins, terpenes, sesquiterpenes, flavonoids, aromatics, dipeptides, phenolics, esterols, germacranolides, secoguaianolides, and several polysaccharides have been isolated from Artemisia species (Valless et al, 2011). In recent years, increasing evidence has shown that sesquiterpene lactones are one of the constituents that impart a wide-range of pharmacological effects, including anti-cancer and immunomodulatory actions (Choi et al, 2011;Kim et al, 2002;Lu et al, 2009;Yang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It's known that DHA induces cancer cell apoptosis via caspase-3-dependent mitochondrial pathway (Lu et al, 2009) To determine whether caspase-3 was involved in DHA and Dic co-induced apoptosis, cells were preincubated with 10 μM z-DQMD-fmk for 1 h before drugs treatment. As shown in Figure 6, pretreatment with z-DQMD-fmk significantly attenuated not only DHAinduced apoptosis but also Dic and DHA co-induced apoptosis, implying that caspase-3 play an important role in Dic and DHA co-induced A549 cell apoptosis.…”
Section: Dha Enhances Dic-induced Cell Apoptosis Via Caspase-3 Dependmentioning
confidence: 99%
“…Many studies showed that DHA can inhibit proliferation and induce apoptosis via caspase-3-dependent mitochondrial pathway (Lu et al, 2009). However, it is not unclear whether Dic and DHA have synergistic effect on inducing cancer cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The Artemisia genus has been used in folk medicine for many years; numerous reports have indicated a vast range of biological effects associated with different Artemisia species (Abad Martinez et al, 2012;Choi et al, 2013). Among the various chemical agents found in these plants, sesquiterpene lactones have been proven to impart anticancer effects (Tan et al, 1998;Firestone et al, 2009;Firestone 2009;Lu 2009;Zhai 2010;Feng 2013).…”
Section: Discussionmentioning
confidence: 99%